P243 Characterising new HIV diagnoses in North West Northern Ireland. (30th June 2016) - Convery, Alan; Perry, Melissa
Abstract : Background/introduction: North West Northern Ireland is a predominately rural population. New HIV diagnoses in Northern Ireland are rising. Aim: We sought to characterise the new diagnoses being made in this region. Methods: The service became a consultant-led service on a daily basis in November 2015 and since this date has been offering ongoing care for PLWH. We analysised demographic details of new HIV diagnoses including sex, age and sexual identity. Details regarding the health location of the first positive test and surrogate markers at diagnosis were also recorded. Results: Since November 2015 there have been 7 new HIV diagnoses. Two tested positive within the GU service; external referrals with a new positive test included 1 from General Practice, 1 from Oral Surgery and 3 from Gastroenterology. Of the 7 new diagnoses 6 were in men. All were of white Northern Irish ethnicity. 3 men were MSM and 3 were heterosexual. 6 of the 7 are thought to have acquired their HIV within NI. Age range at diagnosis was 27–64 years old, but 6/7 were 44 years old or over. One patient disengaged from care following diagnosis and no surrogate markers were obtained as a result of patient's refusal for further blood tests. Of the 6 that have remained in care only 1 patient had a baseline CD4 count of greater than 350 cells/mm 3 ; 2 patients had a CD4 < 200 cells/mm 3 at diagnosis. Conclusion: Although small numbers so far, this analysis suggests that new HIV diagnoses in this region are of an older age with advanced HIV.